HLA-A∗03:01 as predictive genetic biomarker for glatiramer acetate treatment response in multiple sclerosis: a retrospective cohort analysis - Zhang, Brian C.; Jarius, Sven; Wildemann, Brigitte (EBioMedicine, 2025)
Background - Glatiramer acetate (GA) is a well-tolerated treatment for multiple sclerosis (MS) and comparable in its efficacy to high-dose interferon beta (IFN). As a lack of validated treatment response biomarkers for MS hampers progress in personalised treatment, the study goal was to search for biomarkers of a successful treatment response utilising the known observation of T-cell expansions after GA treatment. - Methods - T-cell receptor beta chain (TRB) sequencing was performed in 3021 patients with MS: a discovery cohort of 1627 patients with MS, 204 of whom had previously been treated with GA, and then validated in 1394 patients with MS, 424 of whom had previously been treated with GA. Clinical data from 1987 patients with MS treated with GA or IFN and available HLA information from the NationMS, ACP, EPIC, BIONAT, and CombiRx trial cohorts were used for a subsequent analysis. - Findings - Common GA-associated TRB expansions were exclusively detected in HLA-A∗03:01 or in HLA-DRB1∗15:01 backgrounds, within CD8+ effector- or CD4+ central-memory T cells. Both sets of common sequences clonally expanded after GA treatment in a first validation cohort and predicted GA exposure in two further validation cohorts. To evaluate whether restriction of public TRBs to only two HLA alleles is also associated with GA’s clinical efficacy, we analysed five cohorts of patients with MS for a potential benefit of the two HLAs concerning the GA response compared to IFN. We consistently found positive interactions with HLA-A∗03:01. This included a relative reduction in relapse risk compared to IFN in HLA-A∗03:01 carriers of 33% (CombiRx: GA + IFN arm: HR 0.67 [95% CI: 0.47-0.96], p = 0.0269) and 34% (CombiRx: GA arm: HR 0.66 [95% CI: 0.45-0.98], p = 0.0377), and in risk to first relapse of 63% (NationMS: HR 0.37 [95% CI: 0.16-0.88], p = 0.0246), but no positive association with DRB1∗15:01. - Interpretation - HLA-A∗03:01 carrying patients with MS specifically benefit from GA treatment and GA significantly outperforms IFN in these patients. Therefore, determining HLA-A∗03:01 status before choosing a platform treatment for MS, would allow for a personalised treatment decision between GA and IFN. - Funding - German Research Foundation, National Institutes of Health, National Multiple Sclerosis Society, Valhalla Foundation, Westridge Foundation, Mayer Foundation, German Federal Ministry of Education and Research.
Online verfügbar 31 July 2025, Version des Artikels 31 July 2025
Gesehen am 07.01.2026